2020
DOI: 10.1590/0102-311x00081319
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend of tuberculosis in Brazil

Abstract: The objective was to analyze the temporal trend of tuberculosis incidence rates in Brazilian states and regions to identify patterns and inequalities. We carried out an ecological study of incidence rates per 100,000 inhabitants aged between 20 and 59 years with tuberculosis in Brazil and in their respective states from 2001 to 2017 according to annual percentage change and joinpoint regression. A significant decrease of -15.1% in the annual variation (95%CI: -27.2; -1.0) was observed in Roraima betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
2
6
0
4
Order By: Relevance
“…1 ), that there was a decrease in the cases of TB in the years 2003, 2008, 2013, 2015 and 2017, demonstrating a pronounced decrease in cases. This reduction in cases is consistent with the temporal trend of TB in Brazil, showing a fall in its incidence in the country’s geopolitical regions [ 27 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…1 ), that there was a decrease in the cases of TB in the years 2003, 2008, 2013, 2015 and 2017, demonstrating a pronounced decrease in cases. This reduction in cases is consistent with the temporal trend of TB in Brazil, showing a fall in its incidence in the country’s geopolitical regions [ 27 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…The results of the study also showed, especially in the trend graphs (Figure 1), that there was a decrease in the cases of tuberculosis in the years 2003, 2008, 2013, 2015, 2017 and 2019, demonstrating a pronounced decrease in cases. This reduction in cases is consistent with the temporal trend of tuberculosis in Brazil, showing a fall in its incidence in the country's geopolitical regions [26,38,39].…”
Section: Discussionsupporting
confidence: 85%
“…The Brazilian National Health System (SUS in Portuguese) may have contributed to this reduction by free access to tuberculosis diagnosis, treatment and adherence since 2003. 12 The service coverage index of primary health care in Brazil ranked the highest from 2000 to 2010 among the BRCIS, which might contribute to the quick control of tuberculosis mortality. 13 Another contributor to reduced tuberculosis mortality might be multisectoral interventions to address health and poverty issues.…”
Section: Discussionmentioning
confidence: 99%